Clinical Scenario and Long‐Term Outcome of Childhood Takayasu Arteritis Undergoing 121 Endovascular Interventions: A Large Cohort Over a Fifteen‐Year Period. Issue 11 (13th October 2021) - Fan, Luyun; Yang, Lirui; Wei, Dongmei; Ma, Wenjun; Lou, Ying; Song, Lei; Bian, Jin; Zhang, Huimin; Cai, Jun
Abstract : Objective: Evidence‐based studies on endovascular approaches for childhood Takayasu arteritis (TAK) are limited. Our objective was to present the largest current real‐world scenario for patients with childhood TAK undergoing interventions and their postinterventional outcomes. Methods: Data were collected for patients with childhood TAK admitted from 2002 to 2017. Complication/reintervention‐free survival was projected by Kaplan‐Meier methods. Associated factors for intervention and predictors for postinterventional complications/reinterventions were assessed via regression models. Results: Among 101 patients enrolled, 69 (68.3%) underwent 121 interventions (angioplasty 95, stenting 26) during a 3.1‐year follow‐up. Compared with the nonintervention group, the intervention group independently associated with a male population (odds ratio [OR] 0.27, P = 0.035) and type IV disease (OR 17.92, P = 0.001). Male sex also marginally indicated a risk for reintervention (hazard ratio [HR] 3.22, P = 0.05). Baseline retinopathy, delay in diagnosis, and descending thoracic aorta involvement were associated with stent insertion ( P < 0.05). Hypertension secondary to renal artery stenosis (RAS; 59.4%) or mid‐aorta stenosis (MAS; 14.5%), heart failure (21.7%), and claudication (21.7%) were leading clinical hints for interventions. The technical success rate was 96.7%. During a median 2.88‐year of follow‐up after intervention, 36 lesions occurred with complications in 28 patients, and 22 lesions in 17 patients, particularly on the renal artery or mid‐aorta. The 5‐year complication‐free and reintervention‐free survivals were 50.7% and 65.8%, respectively. Peri‐interventional dual antiplatelet therapy (DAPT; HR 0.31), concurrent surgery (HR 26.5), and technical failure (HR 3.65) were independent predictors for complications ( P < 0.05). Male sex (HR 2.52), retinopathy secondary to hypertension (HR 3.41), and pulmonary artery hypertension (PAH; HR 3.64) were baseline indicators for complications ( P < 0.05). Conclusion: Over two‐thirds of patients with childhood TAK require interventions, and the 5‐year complication‐free survival is 50.7%. Male sex, retinopathy, and PAH at baseline indicate the possibility of unfavorable outcomes. Interventions on MAS or RAS in childhood TAK raise specific concerns. DAPT peri‐intervention appears to protect patients with childhood TAK from postinterventional complications.